Activity profile of international-level soccer referees during competitive matches - Castagna, C.; Abt, G.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to investigate the activity profile of soccer referees competing at international level. Thirteen international-level soccer referees (INRG, age 38 ± 3 years, height 182.0 ± 6.5 cm, and body mass 78.8 ± 7.0 kg) were observed during official international matches using a match analysis system (Play Controller, Phromos, Italy) that enabled speeds and times collection for 11 arbitrarily chosen match categories. For comparison, 13 Italian elite-level soccer referees (NRG, age 37 ± 3 years, height 182.5 ± 3.5 cm, and body mass 77.1 ± 6.5 kg) were examined during domestic official first division matches (Serie A). Results showed that NRG covered more distance during matches than the INRG (12,956 ± 548 m and 11,218± 1,056 m, respectively; p < 0.05). Running faster than 18 km·h-1, NRG covered more distance than INRG (2,378 ± 423 m and 1,642 ± 689 m, respectively; p < 0.05). No between-halves differences in the distance covered at speed faster than 18 km·h-1 were observed in each group. The main finding of this study is that international-level referees during international competitions are less active than national-level officials directing domestic matches. This unexpected result may suggest the need for specific training for the international referees, as recent reports have shown that better positioning is associated with longer space coverage during competitive matches. Across-halves, high-intensity, space-coverage conservation should be regarded as a peculiarity of the elite-level soccer referee.